The diversity of capitalism − specificity of Chinese model - Pęciak, Renata (Różnorodność kapitalizmu – specyfika modelu chińskiego, 2019)
From the perspective of institutional economics within which the research concerning capitalism diversity is conducted, the capitalist system is not homogenous, and a universal model of a capitalist economy cannot be indicated. According to several researchers, the nature of capitalism implies the policy, whereas the nature of interactions between the political and social spheres is decisive for the capitalist system. The shift of economic power to emerging markets caused an increased interest in these economies and a search for the models of capitalism distinctive for them. The paper aims to present selected approaches to research on capitalism diversity and to explain the specific character of the model of capitalism from this perspective. The paper contributes to the understanding of the complexity of the Chinese socio-economic system, while emphasising the specific synergy between politics and economics
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 143-153
Keywords: capitalism; China; political economy; regulation school; variety of capitalism; kapitalizm; różnorodność kapitalizmu; Chiny; ekonomia polityczna; szkoła regulacji